2020
DOI: 10.1007/s13201-019-1131-5
|View full text |Cite
|
Sign up to set email alerts
|

Pollution potential and causative hydrogeochemical processes in unconfined aquifer systems in a typical urban setting: emphasis on recharge and discharge areas

Abstract: The inhabitants of Akure Metropolis, southwestern Nigeria, depend solely on groundwater for their domestic, industrial and irrigation purposes. There is a need to delineate recharge and discharge areas for assessment and management of groundwater in these areas. One hundred and ninety (190) dug wells were selected for this assessment. Elevation and water table data aided accurate delineation of recharge, discharge and groundwater divide areas. Thirty-six wells representative of recharge and discharge areas wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In other words, when one variable changed, another changed in a completely unrelated manner. This shows that human activity is the primary source of heavy metals in groundwater as well (Eyankware et Statistical approach to health risk assessment A sample of questionnaire was designed and administered to fty ve ( 55) persons to determine the potential health risk of water on the inhabitants of the area in the last ten (10) years. The result showed that certain percentage of the sampled people have suffered or experienced every common water borne diseases listed in the questionnaire, namely; diarrhea, typhoid fever, cholera, dysentery, hepatitis A and Giardia (Table 12).…”
Section: Correlation Matrixmentioning
confidence: 99%
“…In other words, when one variable changed, another changed in a completely unrelated manner. This shows that human activity is the primary source of heavy metals in groundwater as well (Eyankware et Statistical approach to health risk assessment A sample of questionnaire was designed and administered to fty ve ( 55) persons to determine the potential health risk of water on the inhabitants of the area in the last ten (10) years. The result showed that certain percentage of the sampled people have suffered or experienced every common water borne diseases listed in the questionnaire, namely; diarrhea, typhoid fever, cholera, dysentery, hepatitis A and Giardia (Table 12).…”
Section: Correlation Matrixmentioning
confidence: 99%
“…The use of contaminated water has had serious negative impacts on vegetation, people and other living things 6 . In developing nations, the local population's most dependable source of clean water, which is groundwater, is being rapidly polluted by industrial discharges of both organic and inorganic effluent 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of polluted waters has resulted in severe adverse effects on plants, humans, and living organisms in general (Ezemonye et al 2019;Lellis et al 2019). Groundwater which is the most reliable source of clean water for use by the local population in developing countries is rapidly being polluted from the agricultural application of pesticides and fertilizers, as well as from organic and inorganic effluent discharge from industries (Edokpayi et al 2018;Kiwaan et al 2020;Asiwaju-Bello et al 2020). In recent years, toxic pollutants were found to be present in unacceptable quantities in water in some developing countries, which poses a serious health threat to the local population (Ahmad and Danish 2018;Imran et al 2020).…”
Section: Introductionmentioning
confidence: 99%